International Trade and Maritime Transport in North America: An Analysis of Productivity and Foreign Direct Investment (2022)
Port logistics activity is a vital element in foreign trade. In a globalized environment that demands greater competitiveness, trade agreements and synergies between trade blocs through maritime transport allow commercial development between economies. This research analyzes the relationship between international trade through seaports and investment in the countries that make up the North American Free Trade Agreement (NAFTA) from 1997 to 2017. An econometric panel data model is used to measure the relationship between the variables, and unit root tests, cointegration tests (Kao and Fisher-Johansen tests), and heterogeneous causality tests (Hurlin and Dumitrescu test) are performed. The results show a positive relationship between trade and productivity, as well as a positive relationship between commerce and direct foreign investment; hence, an increase in investment causes a growth in international trade between Mexico, the United States, and Canada. JEL Codes: F40 Received: 18/04/2022.  Accepted: 26/07/2022.  Published: 01/12/2022.